MESIN PANEN PADI PORTABEL TIPE KNAPSACK - HR. Hutagalung; hersyamsi hersyamsi; puspitahati puspitahati (Universitas Sriwijaya, 2012)
The objective of this research was to design and test the rice harvest machine portable knapsack type. The methods used in this research were engineering design, making equipment, and testing on the equipment. The primary paramaters were theoretical capacity of the planting, harvesting effective capacity, work efficiency equipment, and the loss of rice yields. The secondary parameters were the forward speed, the total of operation, and the rice yields. The testing of this machine is done in area rice field with an area of 202 at 10 obsrevation points. Theoretically, the rice harvest machine portable knapsack type was able to finish harvesting of 1 Ha of rice crops with a time of 67.11 hours. Whereas, the effective working capacity of the field tested results showed that this type of harvesting machine was able to finish of 1 Ha with a time of 60.5 hours. From the comparison of harvesting manually and by used the machine (hour/Ha/person) obtained an efficiency of 50.77 % and the loss of grain in process harvesting by used the rice harvest portable knapsack type of 44.4 % Keyword : harvester machine, performance, efficiency